Cloning and expression of a Saccharomyces diastaticus glucoamylase gene in Saccharomyces cerevisiae and Schizosaccharomyces pombe. - Erratt, J A (1986)
A recombinant plasmid pool of the Saccharomyces diastaticus genome was constructed in plasmid YEp13 and used to transform a strain of Saccharomyces cerevisiae. Six transformants were obtained which expressed amylolytic activity. The plasmids each contained a 3.9-kilobase (kb) BamHI fragment, and all of these fragments were cloned in the same orientations and had identical restriction maps, which differed from the map of the STA1 gene (I. Yamashita and S. Fukui, Agric. Biol. Chem. 47:2689-2692, 1983). The glucoamylase activity exhibited by all S. cerevisiae transformants was approximately 100 times less than that of the donor strain. An even lower level of activity was obtained when the recombinant plasmid was introduced into Schizosaccharomyces pombe. No expression was observed in Escherichia coli. The 3.9-kb BamHI fragment hybridized to two sequences (4.4 and 3.9 kb) in BamHI-digested S. diastaticus DNA, regardless of which DEX (STA) gene S. diastaticus contained, and one sequence (3.9 kb) in BamHI-digested S. cerevisiae DNA. Tetrad analysis of crosses involving untransformed S. cerevisiae and S. diastaticus indicated that the 4.4-kb homologous sequence cosegregated with the glucoamylase activity, whereas the 3.9-kb fragment was present in each of the meiotic products. Poly(A)+ RNA fractions from vegetative and sporulating diploid cultures of S. cerevisiae and S. diastaticus were probed with the 3.9-kb BamHI fragment. Two RNA species, measuring 2.1 and 1.5 kb, were found in both the vegetative and sporulating cultures of S. diastaticus, whereas one 1.5-kb species was present only in the RNA from sporulating cultures of S. cerevisiae.